The Spread of the Lengthening Time Effect of Emotions in Memory: A Test in the Setting of the Central Tendency Effect - Droit-Volet, Sylvie; Gil, Sandrine (Frontiers in Psychology, 2021)
The aim of the present study was to test how the perception of an emotional stimulus colors the temporal context of judgment and modifies the participant’s perception of the current neutral duration. Participants were given two ready-set-go tasks consisting of a distribution of short (0.5 to 0.9 s) or long sample intervals (0.9 to 1.3 s) with an overlapping 0.9-s interval. Additional intervals were introduced in the temporal distribution. These were neutral for the two temporal tasks in a control condition and emotional for the short, but not the long temporal task in an emotion condition. The results indicated a replication of a kind of Vierordt’s law in the control condition, i.e., the temporal judgment toward the mean of the distribution of sample intervals (central tendency effect). However, there was a shift in the central tendency effect in the emotion condition indicating a general bias in the form of an overestimation of current intervals linked to the presence of a few emotional stimuli among the previous intervals. This finding is entirely consistent with timing mechanisms driven by prior duration context, particularly experience of prior emotional duration. Key-words: Time; Emotion; Memory; Context; Central tendency effect